Optimization of Polysaccharide Extraction from Gracilaria fisheri Using Response Surface Methodology - อวะภาค ดาริกา; มะเห นพรัตน์; พิชัยรัตน์ ดลฤดี (KKU Science Journal, 2013)
Response Surface Methodology (RSM) was used to determine optimum condition for Gracilaria fisheri polysaccharides extraction. Box-Behnken experimental design was applied to optimized the ratio of water to algae, extraction time and number of extraction. The results showed that these three factors affected yield of polysaccharide extraction. The experimental data obtained were fitted to quadratic equation because it showed high coefficient of determination (R2 = 0.915). The 3-D response surface plot and the contour plot derived from the mathematical models were applied to determine the optimal conditions. The optimum extraction conditions were as follows: number of extraction 3, ratio of water to algae 1:35, and extraction time 60 minutes. Under the optimal condition, the polysaccharide extraction yield was 63.23 g /100 g algae.